2017
DOI: 10.1016/j.matbio.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

A step towards clinical application of acellular matrix: A clue from macrophage polarization

Abstract: The outcome of tissue engineered organ transplants depends on the capacity of the biomaterial to promote a pro-healing response once implanted in vivo. Multiple studies, including ours, have demonstrated the possibility of using the extracellular matrix (ECM) of animal organs as platform for tissue engineering and more recently, discarded human organs have also been proposed as scaffold source. In contrast to artificial biomaterials, natural ECM has the advantage of undergoing continuous remodeling which allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…Interestingly enough, natural ECM-based scaffolds obtained from human organs that are being used as supporting scaffolding material for bioengineered tissues, have been reported to contain significant amount of TGF-beta [127][128][129][130] and to be able to induce T-cell apoptosis and promote conversion of naïve CD4 + T cells into CD4 + CD25 + Foxp3 + Treg [118,129]. This observation is consistent with the evidence showing that the ECM possesses strong immunomodulatory properties.…”
Section: Regenerative Immunologysupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly enough, natural ECM-based scaffolds obtained from human organs that are being used as supporting scaffolding material for bioengineered tissues, have been reported to contain significant amount of TGF-beta [127][128][129][130] and to be able to induce T-cell apoptosis and promote conversion of naïve CD4 + T cells into CD4 + CD25 + Foxp3 + Treg [118,129]. This observation is consistent with the evidence showing that the ECM possesses strong immunomodulatory properties.…”
Section: Regenerative Immunologysupporting
confidence: 78%
“…Studies in rats showed that rabbit acellular decellularized muscle scaffolds down-regulated T cell xenogeneic responses and T H 1 effector function compared to fresh tissue by inducing a state of peripheral T cell hyporesponsiveness [131]. Moreover, ECM obtained from human normal or diseased organs, promote a protolerogenic macrophage polarization similar to the one that is observed in the adaptive regenerative healing response whereby a phenotypic transition from the pro-inflammatory M1 to the immune-modulating M2 phenotype occurs [128,132,133]. Therefore, combining the intrinsic ability of PSC-differentiated tissue to release TGF-beta with the immunomodulatory properties of ECMbased scaffolds, may represent a valuable strategy to reduce immunogenicity of bioengeneered organs.…”
Section: Regenerative Immunologymentioning
confidence: 99%
“…Once equilibrium was reached, the valve to the treatment chamber (7), which contained the porcine aorta (8), was opened, and CO 2 flow was programmed to 1 mL/min at the pump inlet. During treatment, the environmental chamber (4) (LU-113 model, ESPEC Corp., Osaka, Japan) was used to maintain the temperature at either 10 or 37°C, and a back-pressure regulator (11) (TESCOM, Elk River, MN) was used to keep the CO 2 pressure in the vessels constant at either 10.3 or 27.6 MPa (1500 or 4000 psi).…”
Section: Decellularization With Supercritical Comentioning
confidence: 99%
“…This is a particular strength of naturally-derived biomaterials, which have recently been shown to promote constructive remodeling during tissue growth [4,5]. Decellularized ECM has also been shown to elicit an anti-inflammatory immune response, which may be related to a reduced risk of rejection [6,7]. Decellularization is accomplished using a variety of techniques, including physical [8], chemical [9], and enzymatic treatment methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…Petrosyan et al . studied the effects of monocytes on different ECM in mice including acellular ECM scaffolds obtained from wild‐type kidneys as well as from kidneys of mice affected by Alport syndrome at different time points of disease progression. Results showed that both healthy and diseased ECM scaffolds induce differentiation of macrophages into reparative M2 macrophages, whereas artificial biomaterials favored differentiation into the M1 phenotype.…”
Section: Immune Response Against Xenogeneic and Allogeneic Scaffoldsmentioning
confidence: 99%